Perceiving Dynamic Emotions Expressed Simultaneously in the Face and Body Minimizes Perceptual Differences Between Young and Older Adults. (12th April 2021) - Abo Foul, Yasmin; Eitan, Renana; Mortillaro, Marcello; Aviezer, Hillel
Abstract: Objectives: It is commonly argued that older adults show difficulties in standardized tasks of emotional expression perception, yet most previous works relied on classic sets of static, decontextualized, and stereotypical facial expressions. In real life, facial expressions are dynamic and embedded in a rich context, 2 key factors that may aid emotion perception. Specifically, body language provides important affective cues that may disambiguate facial movements. Method: We compared emotion perception of dynamic faces, bodies, and their combination in a sample of older (age 60–83, n = 126) and young (age 18–30, n = 124) adults. We used the Geneva Multimodal Emotion Portrayals set, which includes a full view of expressers' faces and bodies, displaying a diverse range of positive and negative emotions, portrayed dynamically and holistically in a nonstereotypical, unconstrained manner. Critically, we digitally manipulated the dynamic cue such that perceivers viewed isolated faces (without bodies), isolated bodies (without faces), or faces with bodies. Results: Older adults showed better perception of positive and negative dynamic facial expressions, while young adults showed better perception of positive isolated dynamic bodily expressions. Importantly, emotion perception of faces with bodies was comparable across ages. Discussion: Dynamic emotion perception in young and older adults may be more similar than previously assumed, especially when the task is more realistic and ecological. Our results emphasize the importance of contextualized and ecological tasks in emotion perception across ages.